Riset Kebutuhan Pengguna Terhadap Sistem Absesnsi dan Penjadwalan Mata Kuliah Kampus - Naufal Andika Rahman; Yogha Satria Nugraha (Aisyah Journal Of Informatics and Electrical Engineering (A.J.I.E.E), 2021)
It is important for a university to pay attention to academic services for students. This is so that the teaching and learning process can run well in line with the rapid development of technology, all aspects of life have adopted the sophistication of information technology, including in the field of education. Many platforms are competing to innovate and create media that can accommodate the needs of many people, especially in education. The positive impacts that arise include the use of information technology to make the management of the assessment results data more efficient. In addition, by utilizing information technology, meeting the need for educational facilities runs quickly. The results of this research can be a source of reference to get information about user needs, thus encouraging the creation of a solution by utilizing the sophistication of information technology (IT) in the world of education. The adoption of information technology is expected to increase efficiency in campus academic services. The research was conducted by interviewing students to get a more specific and personalized view. From the results of the interview was taken measurements to find out how many students feel the same and consider the aspects that support the development of information technology in the form of applications that are able to answer academic service problems.